Cholestasis secondary to progesterone. (18th April 2012) - Roberts, L; Cramp, M; Montague, I
Abstract : Obstetric cholestasis (OC) normally presents in late pregnancy with itching and raised transaminases. Jaundice is uncommon. Oestrogen metabolites have long been shown to exhibit a cholestatic effect on the liver and an imbalance of progesterone metabolites is believed to be contributory to the pathogenesis of OC due to their effect on biliary canalicular transport systems. Cholestatic jaundice related to the combined oral contraceptive pill is a risk factor for cholestasis during pregnancy. Progesterone in isolation has not previously been reported as a cause of OC. We present a case in which progesterone is believed to be causal in the development of OC. At 14 years of age the patient presented with clinical jaundice, pruritis and vomiting, four weeks after commencing norethisterone. Investigations revealed a cholestatic picture. Infection screen and ultrasound scan were normal. Liver function tests normalised within 4 weeks of stopping norethisterone. Aged 22, She patient underwent a cholecystectomy for multiple gall stones. Aged 24 she presented in her first pregnancy at 17 weeks gestation with clinical jaundice and pruritis. Investigations revealed raised transaminases, bilirubin and bile acids. A diagnosis of OC was made after excluding other causes for her condition. Transaminases, bile salts and bilirubin levels normalised after the patient was commenced on ursodeoxycholic acid and vitamin k. Antenatal monitoring included serial growth scans, regular blood profiles, and induction of labour at 37 weeks gestation. Her post delivery liver status is awaited.